2003
DOI: 10.1038/sj.ijo.0802248
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among the β2- and β3- adrenergic receptor genes and total body fat and abdominal fat level in the HERITAGE Family Study

Abstract: OBJECTIVE AND SUBJECTS:Interactions between markers in the b2-and b3-adrenergic receptor (ADR) genes and total body fat and computerized tomography-measured abdominal fat phenotypes were studied in the HERITAGE Family Study cohort of Black (n ¼ 205; 81 males and 124 females) and White (n ¼ 415; 198 males and 217 females) subjects before and after an endurance training program. RESULTS: In Black subjects, b2-and b3-ADR gene variants showed evidence of interactions on changes in total body fat mass and abdominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
2
10
2
Order By: Relevance
“…Interaction between β3AR Trp64Arg and UCP1 -3826A>G was reportedly related to weight gain [12], resistance to weight loss [13] and lower BMR [14]. Interaction between β3AR Trp64Arg and β2AR Arg16Gly was reported to be associated with changes in fat mass and abdominal adiposity to training [15]. Despite the reports on these interactions, the relationship among three polymorphisms of β3AR Trp64Arg, β2AR Arg16Gly and UCP1 -3826A>G for obesity remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction between β3AR Trp64Arg and UCP1 -3826A>G was reportedly related to weight gain [12], resistance to weight loss [13] and lower BMR [14]. Interaction between β3AR Trp64Arg and β2AR Arg16Gly was reported to be associated with changes in fat mass and abdominal adiposity to training [15]. Despite the reports on these interactions, the relationship among three polymorphisms of β3AR Trp64Arg, β2AR Arg16Gly and UCP1 -3826A>G for obesity remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Synergic effect of β3AR Trp64Arg and UCP1 -3826A>G was demonstrated in the studies showing both β3AR Arg allele and UCP1 G allele were related to weight gain [12], resistance to weight loss [13] and lower BMR [14]. In regard to the interaction between β3AR Trp64Arg and β2AR Arg16Gly, both β3AR Arg allele and β2AR Arg allele carriers in Black subjects made the total fat mass and total abdominal fat significantly lower after training in HERITAGE study, suggesting that the carriers of β3AR Arg and β2AR Arg alleles might reduce abdominal fat easily [15]. The carriers of β3AR Arg/Arg and β2AR Arg/Arg genotypes in the present study also tended to have low waist circumference and waist to hip ratio.…”
Section: Discussionmentioning
confidence: 99%
“…26 Two recent reports addressing the relationship between ADRB2 and fat measures quantified by CT from the HERITAGE study have produced evidence for association, but only in subgroups. The first 27 examined the Arg16Gly, but not the Gln27Glu, polymorphism with respect to response to endurance training in AA and Caucasian subjects, reporting no significant main-effect association between this polymorphism and change in CTmeasured visceral fat area, although they did report an interaction between Arg16Gly and a polymorphism in the beta-3 adrenergic receptor on change in total abdominal fat area. In the second study 12 the Gln27Glu polymorphism was found to be associated with baseline total fat mass in obese men, with higher mean fat mass associated with the Gln27 allele (P ¼ 0.0001 for genotype-by-obesity interaction).…”
Section: Discussionmentioning
confidence: 99%
“…Research investigating the relationship between ADRB2 and more direct measures of fat deposition, such as computed tomography (CT)-assessed visceral and subcutaneous fat mass, however, has been limited. A small twin study 26 and one report from the HERITAGE study 27 have provided some evidence of an effect of this gene on regional fat distribution. Both of these studies were interventional; however, with the first examining response to overfeeding and the second assessing response to endurance training.…”
mentioning
confidence: 99%
“…43,44 Similarly, in another survey, an interaction was described between changes in fat mass and abdominal adiposity during a training program and ADRB3 polymorphism-Trp64Arg and ADRB2 polymorphism-Arg16Gly. 45 In a study by Tsunekawa et al, 46 significant differences were observed between combinations of the ADRB3 polymorphisms Trp64Arg, ADRB2 Arg16Gly, and uncoupling protein 1 UCP1-3826 A/G (mitochondrial, proton carrier) and hip/ waist ratio.…”
mentioning
confidence: 99%